Potentiality of standardized extract and isolated flavonoids from Zuccagnia punctata for the treatment of respiratory infections by Streptococcus pneumoniae: in vitro and in vivo studies - Zampini, Iris Catiana (2012)
Ethnopharmacological relevance: Zuccagnia punctata Cav. (Fabaceae) is a monotypic species distributed in western Argentina and is traditionally used for the treatment of bacterial and fungal infections. The aim of this study was to demonstrated the antibacterial activity of the Zuccagnia punctata standardizedextract and the structurally related non-methoxylated flavonoids with similar pattern of substitution and differences in ring C present in this plant species: 7-hydroxyflavanone (HF), 2",4"-dihydroxychalcone (DHC) and 3,7-dihydroxyflavone (DHF), against Streptococcus pneumoniae clinical isolates using in vitro and in vivo models. Materials and Methods: MIC values of natural products were determined by agar macrodilution method. In vivo activities were investigated in a Streptococcus pneumoniae infection model in mice. Lung and blood samples were obtained for bacterial cell counts. The serum was used by biochemical analysis (alanine transaminase, aspartate transaminase, urea and creatinine) in order to evaluate the toxicity of natural products. Results: All samples showed antimicrobial activity in vitro with MIC values between 50 and 500 ug/ml.Zuccagnia punctata extract (1 mg/mice) and HF (1 mg/mice) significantly reduced the number of viable Streptococcus pneumoniae in lung (p < 0.01) while lower quantities has not effect. Therefore, the present study has shown that intake once or twice a day of 1 mg of Zuccagnia punctata extract or HF for sevendays did not result in toxicity. Conclusions: Our results showed that Zuccagnia punctata extract as well as one of its isolated flavonoids, 7-hydroxyflavanone, could be useful for the development of a novel respiratory infections treatment.